Implementasi Supervisi Akademik berbasis Refleksi Kolaboratif: Optimalisasi Pembelajaran Guru Tamu Industri di SMKN 5 Banjarmasin - Edi Fakhrin; Ahmad Suriansyah; Aslamiah Aslamiah (LPPM Institut Pendidikan Nusantara Global, 2026)
This study addresses a persistent challenge in Indonesian vocational education, namely bridging the gap between classroom instruction and the rapidly evolving demands of industry within the link and match policy framework. The study aims to analyze the implementation of a collaborative reflection-based academic supervision model that integrates industrial guest teacher sessions into a structured supervision cycle to enhance the pedagogical competence of productive teachers at SMKN 5 Banjarmasin. Industrial guest teaching sessions were positioned as the initial trigger for supervision, followed by systematic classroom observation, reflective Focus Group Discussions, and pedagogical redesign through lesson plan revision. Using a qualitative approach with a participatory action research design, the study was conducted over six months and involved 12 productive teachers from the Automotive Engineering program. Data were collected through participatory observations of industrial guest sessions, structured FGDs using a modified design thinking framework, teacher reflection journals, lesson plan document analysis, and in-depth interviews. The findings indicate notable improvements in teachers’ pedagogical competencies, particularly in adapting industrial content into lesson plans (75%), applying problem-solving-based instructional strategies (70%), and developing contextual learning media (65%). Beyond individual competence enhancement, the supervision model fostered a sustainable Professional Learning Community (PLC), shifting teacher practices from individualistic to collaborative and inquiry-oriented. In addition, the model facilitated a transformation in the principal’s role from conventional supervision toward instructional leadership. Overall, the study concludes that collaborative reflection-based academic supervision embedded within industrial guest teacher programs offers an effective and transferable framework for strengthening institutional learning cultures responsive to industry demands.